Myth a very short introduction - Segal, Robert Alan 1948-2024 (Very short introductions, 2015)
This title introduces a wide array of approaches to understanding myth from varied disciplines. It uses the famous ancient myth of Adonis to analyse the ideas and individual approaches and theories of theorists such as Sigmund Freud, Claude L evi-Strauss, Albert Camus, and Roland Barthes. This new edition considers the interactions of myth theory with cognitive science, the implications of the myth of Gaia, and the differences between story-telling and myth, as well as the future study of myth